Standard test method for Direct Current Magnetic Properties of Materials Using D-C Permeameters and the Ballistic Test Methods (American Society of Testing Materials, 2005)
This test method provides dc permeameter tests for the basic magnetic properties of materials in the form of bars, rods, wire, or strip specimens which may be cut, machined, or ground from cast, compacted, sintered, forged, extruded, rolled, or other fabricated materials.